Structure-guided design of artificial metalloenzymes based on alcohol dehydrogenase for transfer hydrogenation - Padley, Henry (2024)
Artificial metalloenzymes (ArMs) combine the advantages of enzyme and synthetic catalysts to offer novel solutions to the synthesis of high-value fine chemicals. ArMs are assembled by incorporation of an organometallic catalyst into a protein scaffold. This enables the exertion of control over the chemical environment of the catalyst via genetic manipulation of the scaffold, providing one of the key advantages of ArMs over small-molecule catalysts. However, rational genetic optimisation requires an understanding of the interactions between the protein, catalyst, and substrate within the ArM. The incompleteness of such knowledge has been highlighted as a relative gap for exploitation within the wider ArM field. In particular, there is little structural information available on ArMs based on enzymatic scaffolds. These systems offer a promising alternative to highly successful ArMs based on non-enzymatic scaffolds. The naturally evolved architecture of the enzyme can be used to the advantage of ArM catalyst or substrate binding.